Effect of Soybean Straw and Seaweed (Sargassum johnstonii) Based Total Mixed Ration on Feed Intake, Digestibility and Rumen Fermentation in Crossbred Cows - Pandya, P R; Katwal, Sarishti; Sorathiya, K K; Patel, Y.G.; Shah, S.V.; Parmar, D.J. (Indian Journal of Animal Nutrition, 2022)
An experiment was conducted to evaluate the effect of soybean straw and seaweed supplementation on feed intake, nutrient digestibility and rumen fermentation in lactating crossbred cows. Six Holstein Friesian X Kankrej (50:50) crossbred cows were used in Switch over design for 135 days with three periods each of 45 days duration. The animals received three treatments as total mixed ration viz., T1: TMR with compound concentrate mixture (60%) and wheat straw (40%); T2: TMR with compound concentrate mixture (60%), wheat straw (20%) and soybean straw (20%); T3: TMR with 8% seaweed (Sargassum johnstonii). The DM and DCP intake were at par in T1 and T2 but significantly (P<0.05) low in T3 while TDN intake differed significantly (P<0.05) among all groups. There was no significant difference in nutrient digestibility except low DM digestibility in T3. Similarly, rumen parameters were also similar among the treatments except TVFA which was significantly lower in T3. Microbial protein was also similar in all the groups. The study revealed low feed intake, TVFA & DM digestibility in seaweed supplemented group. Â